Analysis of Workplace Accident Risk Using The Hazard Identification Risk Assessment and Determining Control (HIRADC) Method in PMKS Pt. Sisirau - Ummarah, Latifa; Irwansyah , Defi; Bakhtiar, Bakhtiar (Faculty of Engineering, Andi Djemma University, 2025)
Work accidents are one of the serious problems that have a direct impact on worker safety and company productivity. This study was conducted at PMKS PT. Sisirau located in Aceh Tamiang. This research aims to explore potential sources of danger, evaluate the degree of associated threats, and formulate strategic preventive measures through the structured framework of Hazard Identification, Risk Assessment, and Control Determination (HIRADC) method. The focus of this study was on three work stations, namely loading ramp, boiling (sterilizer station), and tipler. The data used were in the form of work accident reports from January 2021 to February 2025, as well as the results of observations and interviews in the field. The results of the study showed that there were a total of 18 work activities identified as hazardous, consisting of 8 activities at the loading ramp station, 5 activities at the boiling station (sterilizer), and 5 activities at the tipler station. The results of the risk assessment showed that at the loading ramp station there were 5 activities with One activity presented moderate risk; three others showed low-risk potential. At the boiling station (sterilizer) there were 4 activities with a moderate risk and 1 activity with a low risk. Meanwhile, at the tipler station, among the evaluated activities, one was determined to involve a significant risk factor, whereas two others presented comparatively lower levels of risk, and 2 activities with low risk. Recommended risk control includes 7 activities with engineering control, 9 activities with administrative control, and 10 activities with mandatory Application of individual safety gear.